Real-time geo-Information fusion as one key aspect of Digital Earth - Hillen, Florian; Ehlers, Manfred; Höfle, Bernhard; Reinartz, Peter (European remote sensing - new opportunities for science and practice, 2014)
The Digital Earth vision by Al Gore recently has evolved to a powerful real-time toolbox for various use cases. Nowadays, almost every geo-sensor data can easily be integrated in a Digital Earth application in real-time and near real-time. This can be in-situ sensor data, smartphone sensor data or also high-resolution remote sensing imagery. However, the benefit of combining multiple data sources is only rarely exploited. Remote sensing data, for example, generally cover large areas but do not deliver information for hidden areas (e.g. under bridges, in house) or under cloud cover. In contrast to that, in-situ sensors deliver punctual information only but may provide information for areas that are invisible to remote sensors. Thus, the first idea that comes to mind is to use the advantages of the respective sensor types to eliminate the disadvantages of the other. The real-time aspect is a crucial point in this process, especially for time-critical applications like early warning systems, decision support systems for security issues or precision fertilisation for agricultural areas. To date, there is a lack of usage regarding real-time integration of fused geo-information even though the benefit is obvious. This work will present the information fusion service (IFS) as a standardised way to fuse and integrate real-time geo-sensor data in Digital Earth applications. An example is presented that utilises the concept of the IFS for a recording campaign combining remote sensing and smartphone in-situ data during a football game. In doing so, the benefit of real-time data integration as well as geo-information fusion in general is emphasised.